From Joseph Schacht to G.H.A. Juynboll on the Common Link Theory - Yahya, Mohamad (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2024)
The topic discussed in this article is the intricacies associated with the common link theory. This theory was first introduced by Joseph Schacht and further developed by G.H.A. Juynboll. It was in the hands of Juynboll that this theory showed its strength. This theory has the dictum that argumentum e silentio; and the more perfect the isnÄd, the later the tradition, so that the more transmission lines meet, either leading to or leaving it, the greater the transmitter and transmission has a historical claim. For them, the theory can be used to trace the time of appearance, author, as well as transmitter of the hadith that is the object of their research. This transmitter is called the common link. The logical consequence is that many of the Prophetic traditions cannot be historically accounted for.